Denotements for Morphological Study of the Kidneys and Paramount Considerations - Akhrorkulovich, Dsc Ismatov Tuichiboy; Makhsudovich, Dsc Kurbonov Obid; Oltinbaevich, PhD Makhmudov Kodirbai; Safaralievich, Norkuzieva Sherali; Asliddinovich, Muminov Zhavokhir; Norbekovich, Norkabilov Alisher (Health & Medical Sciences, 2024)
A kidney biopsy is a procedure in which a sample of kidney tissue is removed for microscopic examination. Kidney biopsy has contributed greatly to the classification of intrinsic renal diseases and hence to a better understanding of their pathogenesis. Although there are many studies regarding kidney biopsy. There is little literature regarding the correlation between indications and histopathology especially in Uzbekistan. Patients who had clinical and/or laboratory evidence of renal disease, whose diagnosis was uncertain by noninvasive methods, and who were eligible for renal biopsy underwent renal biopsy.